VD_FINDINFO AA 34/13 - 3/2015 vom 21. Januar 2015 - VD Tribunal cantonal (2015)
ACCIDENT, FRAIS DE TRAITEMENT, INDEMNITÉEN GÉNÉRAL, RENTEEN GÉNÉRAL | 10 LAA, 16 LAA, 18 LAA, 36 LAA, 6 al. 1 LAA, 6 al. 2 LAA, 9 al. 2 OLAA